PENGARUH brand ambassador ANDRE TAULANY TERHADAP MINAT BELI KONSUMEN “INI KERIPIK” - Jeki Setiawan Putra; N. Rachma; M. Hufron (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACKThis research is to describe visibility, credibility, attraction, power and interest in buying and to know the influence visibility, credibility, attraction, power and interest in buying and partial buying interest, this research method uses quantitative methods. This type of research is explanatory research.The sample of this study was buyers of souvenir products